MECHANISMS OF DEFECTMAKING IN SEMICONDUCTOR TAPES OF HALCOGEN LEAD AND TIN - Галущак, Мар'ян Олексійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Influence of inlying mechanical tensions, and also remaining oxygen on processes of defect formation in films of lead chalkogenides, grown on different substrates is considered. It is cleared up mechanism of formation of metallic phase in case of films growing from the vapour phase. A kinetics of surface concentration of electrons taking into account the complex formation of own defects with oxygen is considered.